The Heinz ketchup bottle. - Verhaaf, Marcel, ....- (Amsterdam : Bis, 2011)
Packaging designer and branding expert Marcel Verhaaf tells the surprising story of the Heinz Ketchup bottle. We learn all there is to know about this iconic packaging, the evolution of ketchup, its ingredients, how the Heinz Corporation evolved, and how the packaging and advertising campaigns have changed over the years. Verhaaf has interlaced the story with countless fascinating facts and delightful anecdotes. This is a fun book for anyone who loves Heinz ketchup, as well as designers and advertisers who want to know more about how the history of this world-famous packaging came to be.